Diagnostic accuracy of C-reactive protein and white blood cell counts in the early detection of inflammatory complications after open resection of colorectal cancer: a retrospective study of 1,187 patients - Warschkow, René; Tarantino, Ignazio; Torzewski, Michael; Näf, Franziska; Lange, Jochen; Steffen, Thomas (International journal of colorectal disease, 2011)
Although widely used, there is a lack of evidence concerning the diagnostic accuracy of C-reactive protein (CRP) and white blood cell counts (WBCs) in the postoperative period. The aim of this study was to evaluate the diagnostic accuracy of CRP and WBCs in predicting postoperative inflammatory complications after open resection of colorectal cancer.
Gesehen am 08.11.2022